2022
DOI: 10.1097/pap.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Oral Epithelial Dysplasia: A Review of Diagnostic Criteria for Anatomic Pathologists

Abstract: Oral epithelial dysplasia (OED) represents a spectrum of histologic changes in the oral cavity mucosa that has the potential to transform into oral squamous cell carcinoma. Predicting the risk of malignant transformation is predominantly based on clinicopathologic correlation, histologic examination and grading. OED often poses a diagnostic challenge, primarily due to its histologic mimics and a large number of terminologies used in the literature. The grading system for OED is also fraught with significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…These are predominantly entities characterized by reactive and/or reparative changes in the oral mucosa as seen in response to trauma, inflammation, irradiation, or ulceration. Deficiencies of essential nutrients such as iron, folate, and vitamin B12, may also simulate dysplasia 10 . A recent systematic review reported an absolute paucity of studies exploring the effect of regular calibration of pathologists on the assessment of OED grading 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are predominantly entities characterized by reactive and/or reparative changes in the oral mucosa as seen in response to trauma, inflammation, irradiation, or ulceration. Deficiencies of essential nutrients such as iron, folate, and vitamin B12, may also simulate dysplasia 10 . A recent systematic review reported an absolute paucity of studies exploring the effect of regular calibration of pathologists on the assessment of OED grading 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Deficiencies of essential nutrients such as iron, folate, and vitamin B12, may also simulate dysplasia. 10 A recent systematic review reported an absolute paucity of studies exploring the effect of regular calibration of pathologists on the assessment of OED grading. 11 Hence, the prime objective of this study was to determine whether calibration of practicing oral pathologists on OED grading could improve the reproducibility of the WHO 2017 and the binary OED grading systems.…”
mentioning
confidence: 99%